Introducing direct root‐zone deficit irrigation to conserve water and enhance grape quality in the Pacific Northwest. Issue 5 (4th October 2018) - Jacoby, Peter; Ma, Xiaochi
Abstract : In 2015, a project was launched to evaluate the potential for using a new form of sub‐surface drip irrigation. Rather than applying micro‐irrigation through horizontal buried lines, drip irrigation was delivered into vertical tubes placed 1 to 4 ft into the root‐zone soil. Juice and wine grapes were selected as the model plant systems for these proof‐of‐concept trials. Earn 0.5 CEUs in Soil & Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/575 .